Uncovering the biology of myelin with optical imaging of the live brain - Hill, Robert A. (Glia, 2019)
Myelin has traditionally been considered a static structure that is produced and assembled during early developmental stages. While this characterization is accurate in some contexts, recent studies have revealed that oligodendrocyte generation and patterns of myelination are dynamic and potentially modifiable throughout life. Unique structural and biochemical properties of the myelin sheath provide opportunities for the development and implementation of multimodal label-free and fluorescence optical imaging approaches. When combined with genetically encoded fluorescent tags targeted to distinct cells and subcellular structures, these techniques offer a powerful methodological toolbox for uncovering mechanisms of myelin generation and plasticity in the live brain. Here we discuss recent advances in these approaches that have allowed the discovery of several forms of myelin plasticity in developing and adult nervous systems. Using these techniques long-standing questions related to myelin generation, remodeling and degeneration can now be addressed.